World Bank Research Digest, Vol. 7(2) - World Bank (Washington, DC, 2014)
In this issue: cities: planning, coordinating, and financing for a better future; measuring inequality of opportunity; breaking out of the middle-income trap; real-time macro monitoring and fiscal policy; bank regulation and supervision: a crisis update; how does nationalizing water services affect quality? And what drives investments under the clean development mechanism?